Realising the right to health in private and public law - Hogan, Des (Trinity College (Dublin, Ireland). School of Law, 2013)
The methods used in this thesis were primarily literature-based involving a review of relevant international and national jurisprudence relating to international human rights law, constitutional law, administrative law and the law of tort. Also reviewed was the literature covering these disparate areas, core texts, interpretative comments, commentaries, opinions, theories and responses of commentators. Areas covered include philosophy, jurisprudence, law, medicine, social science and international relations. Most of the research was conducted in Trinity College Dublin and through its extensive on-line electronic catalogues. Some of the research was conducted at the Bodelian Law Library, Oxford University, England. Having worked in the area of human rights for a number of years, the purpose of undertaking the research was to deepen my academic expertise in the field. The research question in this thesis is whether the right to health, as set out under international human rights law, is adequately reflected in domestic Irish law and, in particular, whether domestic law adequately vindicates the right to health through legal accountability where violations of the right occur.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin